(untitled) - Taufikin , Farid Khoeroni , Sanusi , Nurshiam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Technology's rapid progression must not erode local wisdom. To achieve a prosperous life, youths must adhere to noble character as a primary component, in addition to their knowledge and technology. This is relevant to the teaching concept taught by Sunan Kudus, called Gusjigang (Gus: good/noble character, Ji: smart at Ngaji (studying religion), and Gang: trade, business/economy). Through a literature research study, the results of photographing Gusjigang in Ki Hadjar Dewantara's educational philosophy using content analysis and hermeneutics show that Gus (noble character) is the main goal in education, notably inner sovereignty (morals, character). Ji-gang, on the other hand, is the objective of self-education (exoteric dimension), notably mastering science and business/economics. Thus, Gusjigang is local wisdom as a representation of autonomous education, that is, inner and outer autonomy, as an alternative to the freedom of learning policy in Indonesia.